Pengembangan aplikasi media pembelajaran perangkat komputer berbasis augmented reality (AR) - Menrisal Menrisal; Indra Wijaya (Jurnal Konseling dan Pendidikan)
This research aims to design Learning Media Introduction to Computer Devices Using Augmented Reality to facilitate understanding of the material on Computer Devices material. This type of research is R&D (Research & Development) and uses the ADDIE analysis model, with design and development steps (1) Analysis, (2) Design, (3) Development, (4) Implementation and (5) Evaluation. The results of the analysis of the validity test by the validator were obtained at 85.23%, it can be interpreted as valid to use. Analysis of the practicality test was obtained at 95.18%, so it can be interpreted as very practical to use. The results of the analysis of the overall effectiveness test were obtained at 90.72%, so that the level of effectiveness can be interpreted as very effective in use. Thus, the Android-based Augmented Reality learning media as a learning medium has been tested for feasibility, advantages, and can be used in the learning process of computer devices.